2022
DOI: 10.1093/jambio/lxac010
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between rhizobial nodulation and arbuscular mycorrhizal fungal colonization inLotus japonicusroots

Abstract: Aims This study aims to identify main factors that influence the tripartite association of legumes with arbuscular mycorrhiza fungi (AMF) and nitrogen-fixing rhizobia. Methods and Results Concurrent inoculations with Mesorhizobium loti and four AMF strains were performed on the model legume Lotus japonicus. Nodulation was significantly enhanced by all AMF strains, under normal conditions, and by specific AMF strains under hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Rhizobia can also interact with eukaryotic microorganisms such as fungi. A large number of studies have shown the positive effect of AMF on nodulation (Antunes and Goss, 2005;Barea et al, 2005;Pang et al, 2023;Tsikou et al, 2023). Phosphate supply by the fungus seems to be the main factor improving the rhizobiumlegume symbiosis, although other factors such as the modulation of plant hormone levels by fungi, as described for PGPRs, also contribute to increase nodule number and plant biomass.…”
Section: Nodule Indirectmentioning
confidence: 99%
“…Rhizobia can also interact with eukaryotic microorganisms such as fungi. A large number of studies have shown the positive effect of AMF on nodulation (Antunes and Goss, 2005;Barea et al, 2005;Pang et al, 2023;Tsikou et al, 2023). Phosphate supply by the fungus seems to be the main factor improving the rhizobiumlegume symbiosis, although other factors such as the modulation of plant hormone levels by fungi, as described for PGPRs, also contribute to increase nodule number and plant biomass.…”
Section: Nodule Indirectmentioning
confidence: 99%
“…Rhizobia can also interact with eukaryotic microorganisms such as fungi. A large number of studies have shown the positive effect of AMF on nodulation ( Antunes and Goss, 2005 ; Barea et al., 2005 ; Pang et al., 2023 ; Tsikou et al., 2023 ). Phosphate supply by the fungus seems to be the main factor improving the rhizobium-legume symbiosis, although other factors such as the modulation of plant hormone levels by fungi, as described for PGPRs, also contribute to increase nodule number and plant biomass.…”
Section: Microbial Interactions Interfering With the Initiation Of No...mentioning
confidence: 99%
“…We observed an increase in AMF root length colonization when R. tropici was coinoculated with the AMF mixture. Depending on the AMF species, root colonization may be positively, negatively or not significantly affected by the presence of NFB [75]. Tsikou et al [75] found that Mesorhizobium loti favored root colonization of C. etunicatum, while it did not affect F. mosseae.…”
Section: R Tropici Effect and The Possible Mechanisms Influencing Arb...mentioning
confidence: 99%
“…Depending on the AMF species, root colonization may be positively, negatively or not significantly affected by the presence of NFB [75]. Tsikou et al [75] found that Mesorhizobium loti favored root colonization of C. etunicatum, while it did not affect F. mosseae. In our study, R. tropici favored Glomus sp1 over D. bernensis, so in this system, the effect on colonization might dependt on the mycorrhizal species.…”
Section: R Tropici Effect and The Possible Mechanisms Influencing Arb...mentioning
confidence: 99%